IMPROVEMENT OF INVENTORY ACCOUNTING IN BUDGET ORGANIZATIONS - Xolmurodova Durdona Otamurod qizi; Ostonokulov Azamat Abdukarimovich (TADQIQOTLAR, 2025)
Abstract. Inventory accounting is a critical aspect of financial management in budget organizations. Accurate inventory management ensures optimal resource allocation and financial stability. However, many budget organizations struggle to maintain effective inventory accounting practices due to a lack of standardized procedures, technological limitations, and human errors. This article examines the challenges faced by budget organizations in inventory accounting and proposes strategies for improvement. These include implementing standardized procedures, adopting technology, improving employee training, and fostering a culture of continuous improvement. By adopting these recommendations, budget organizations can enhance their inventory accounting practices, leading to increased efficiency and financial stability.